Students' Awareness of Religious Moderation: An Examination of the Effectiveness of Group Format Intelligent Character Education (PKC-KO). - Al Halik (Tarbawi : Jurnal Ilmu Pendidikan, 2023)
In the realm of education, fostering a moderate character is closely tied to the selection of effective strategies. The precision in executing these strategies plays a crucial role in instilling values successfully. The article aims to assess the effectiveness of group-based intelligent character education services (PKC-KO) in improving madrasah students' awareness of religious moderation. The study utilizes an experimental design with a Non-Equivalent Control Group, focusing on Class X students from Madrasah Aliyah Negeri 1 EastLampung, using Purposive Sampling. A Likert scale-based assessment is employed, and the data is analyzed using statistical tools such as the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov 2 Independent Samples with the assistance of SPSS. Overall, the research findings reveal the success of group-based intelligent character education programs in enhancing madrasah students' awareness of religious moderation. There is a notable disparity in the students' awareness of religious moderation before and after receiving PKC-KO in the experimental group. In contrast, the control group, without such educational intervention, did not experience a significant increase in awareness. The study underscores that PKC-KO imparts principles of religious moderation, encouraging students to maintain a balanced perspective, avoid extremism, practice tolerance towards diverse religious backgrounds, dispel stereotypes, develop positive interpersonal skills, and contribute to societal peace by respecting religious distinctions. This research holds educational implications, emphasizing the potential of PKC-KO-based programs for cultivating awareness of religious moderation among madrasah students. The study suggests that implementing PKC-KO can significantly impact students' perspectives on religious moderation, promoting a more harmonious and tolerant society.